Entrepreneurship in Existentialism Philosophy: Examining Life and Business - Agustian Zen; Puspita Puji Rahayu; Muhamad Malik Mutoffar; Wahyuni Sri Astutik; Abu Muna Almaududi Ausat (Innovative: Journal Of Social Science Research, 2023)
In the era of globalisation and increasingly fierce business competition, the success of an entrepreneur is something that is very important and desired by many people. One of the relevant philosophical views to be studied in the context of entrepreneurial thinking is existentialism. This research aims to explore the understanding of the nature of entrepreneurial thinking in the perspective of existentialism philosophy. The focus of this research is qualitative. Methods for gathering information included careful attention and detailed note-taking, with subsequent analysis including data reduction, visualisation, and inference. The results show that entrepreneurial thinking from an existentialist perspective can make a significant contribution to the development of sustainable and socially responsible business theory and practice. An existentialist view can help entrepreneurs to overcome challenges and obstacles in business by developing the ability to derive meaning and purpose from every life experience.